Language Choice in Psychotherapy of Multilingual Clients - Leila Verkerk; Ad Backus; Laurie Faro; Jean-Marc Dewaele; Enny Das (Language and Psychoanalysis, 2021)
Language is an essential part of psychotherapeutic work. In psychotherapy involving more than one language and/or culture, acknowledging the impact of the therapist’s and the client’s language(s) can facilitate achieving the most beneficial therapeutic process and outcome. The field has witnessed a surge in interdisciplinary work combining research methods from multilingualism and psychotherapy. This research aims to investigate the role of multilingualism in emotion expression and interpretation in psychotherapy offered by multilingual/multicultural therapists. Ten individual semi-structured interviews with therapists in the Netherlands focused on therapists’ experience of working as a multilingual/multicultural therapist with culturally and linguistically diverse clients. Thematic analysis of the results showed that language choice influenced the therapeutic process and its outcome in terms of discussing emotional topics, establishing and maintaining rapport with the client, and managing linguistic and cultural differences. Linguistic awareness of therapists allows them to manage the linguistic and cultural issues that inevitably arise in encounters with multilingual/multicultural clients.